Typology and indicators of ecosystem services for marine spatial planning and management - Böhnke-Henrichs, Anne; Baulcomb, Corinne; Koss, Rebecca; Hussain, S. Salman; de Groot, Rudolf S. (Journal of environmental management, 2013)
The ecosystem services concept provides both an analytical and communicative tool to identify and quantify the link between human welfare and the environment, and thus to evaluate the ramifications of management interventions. Marine spatial planning (MSP) and Ecosystem-based Management (EBM) are a form of management intervention that has become increasingly popular and important globally. The ecosystem service concept is rarely applied in marine planning and management to date which we argue is due to the lack of a well-structured, systematic classification and assessment of marine ecosystem services. In this paper we not only develop such a typology but also provide guidance to select appropriate indicators for all relevant ecosystem services. We apply this marine-specific ecosystem service typology to MSP and EBM. We thus provide not only a novel theoretical construct but also show how the ecosystem services concept can be used in marine planning and management. •An application-oriented marine ecosystem service (ES) typology is developed.•It meets the requirements for an application in EBM and marine spatial planning.•It facilitates the implementation of the EU Marine Strategy Framework Directive.•It includes detailed definitions, examples, indicators to facilitate its utilization.